Client Management System with Two Factor Authentication and Anti Input Injection for Asian Life Travels Sdn Bhd - Ramadas, Sanjay; ABDULLAH, ZUBAILE (Applied Information Technology And Computer Science, 2023)
A Client Management System (CMS) is a system that keeps track of a company's particular interactions with its customers. sales, marketing, and support teams. Client Management System is being utilized in majority of industries. One of the key issues that needs immediate attention with majority of existing Client Management System is security issues. Nowadays, everyone is concerned about data. Everyone wants their data to be secured and safe, from the business owner to the average individual with an internet presence. And data has tremendous worth. Your corporate data is the most important asset you have in terms of your business. So, if your selected CMS system leaks your data, it may be a disastrous situation for both you and your organization.